IMPLEMENTASI CHATBOT WHATSAPP UNTUK LAYANAN INFORMASI DESA MENGGUNAKAN TF-IDF DAN COSINE SIMILARITY BERBASIS NATURAL LANGUAGE PROCESSING - Andika Ramadhana; Hery Kristianto; Edwin Hari Agus Prastyo (LPPM UNIVERSITAS BINA INSAN, 2026)
Village information services are still conducted manually, limiting public access to timely information. This study aims to develop a WhatsApp-based chatbot to automate village information services using Natural Language Processing (NLP), TF-IDF, and Cosine Similarity. The system employs a text preprocessing pipeline (case folding, tokenization, stopword removal, stemming), TF-IDF weighting, and similarity matching against a knowledge base of 15 FAQ pairs. Evaluation on 15 test queries yielded an average Cosine Similarity of 0.91, with 14 out of 15 queries exceeding the 0.80 threshold (93.33% success rate). This system contributes to reducing the administrative burden on village staff and improving public service response time.